Development, physiochemical characterization and forming mechanism of Flammulina velutipes polysaccharide-based edible films. (5th November 2016) - Du, Hengjun; Hu, Qiuhui; Yang, Wenjian; Pei, Fei; Kimatu, Benard Muinde; Ma, Ning; Fang, Yong; Cao, Chongjiang; Zhao, Liyan
Highlights: Edible films were prepared with Flammulina velutipes polysaccharide (FVP). The FFS was a pseudoplastic fluid, and had appropriate viscosity for film-forming. The FVP films had desirable mechanical, barrier, and microstructure properties. The formation of FVP films depended on β-glycosidic and hydrogen bonds. FVP is a suitable material for edible film preparation. Abstract: Edible films of Flammulina velutipes polysaccharide were prepared and characterized in terms of rheological, optical, morphologic, mechanical and barrier properties to evaluate their potential application in food packaging. Results suggested that FVP film prepared by the solution of 1:150 (w/v) had the optimal mechanical property, smooth and uniform surface, and good barrier property to water (37.92 ± 2.00 g mm/m 2 h kPa) and oxygen (37.92 ± 2.01 meq/kg). The capacity of film-formation might be related to inter-molecular and intra-molecular hydrogen bonds of FVP and formation of β-glycosidic bonds during the process of film-formation. These findings will contribute to a theoretical basis for the development of FVP film in food packaging.